Peer Learning in Social Media Enhanced Learning Environment - Anne-Maritta Tervakari (International Journal of Emerging Technologies in Learning (iJET), 2012)
TUT Circle, a dedicated social media service for students at Tampere University of Technology (TUT), was used as a learning environment for the purpose of enhancing students‘ collaboration, communication and networking skills required in business and working life and for promoting peer learning in small groups. Unfortunately, active conversation was limited. The students intensively read content created by other students, but they did not actively present their opinions, arguments or comments. Another reason for the lack of real conversation was procrastination. The students seemed to need more encouragement to comment on or question the ideas of others, more support to promote intergroup interaction and more assistance with time management.